Q1: Could someone provide a proof for this equation (please focus on this question):

$$e^z = \lim \limits_{x \rightarrow \infty} \left( 1 + \frac{z}{x} \right)^x$$

Q2: Is there any corelationn between above equation and the equation below (this would benefit me a lot because i at least know how to proove this one):

$$e = \lim \limits_{x \rightarrow \infty} \left( 1 + \frac{1}{x} \right)^x$$


Let $y=x/z$. Then $$ \lim \limits_{x \rightarrow \infty} \left( 1 + \frac{z}{x} \right)^x = \lim \limits_{y \rightarrow \infty} \left( 1 + \frac{1}{y} \right)^{yz} = \left(\lim \limits_{y \rightarrow \infty} \left( 1 + \frac{1}{y} \right)^{y}\right)^z = e^z $$

But note that this assumes that you have a definition of $a^x$ and know that $a^{xy}=(a^x)^y$ and that $x\mapsto a^x$ is continuous.

  • 1
    $\begingroup$ And note that $z$ is considered as constant while $x$ varies, tending to $\infty$, hence $x/z\to\infty$, too. $\endgroup$ – Berci Feb 5 '13 at 17:51
  • $\begingroup$ Nicely shown but I still need anwser to Q1. $\endgroup$ – 71GA Feb 5 '13 at 18:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.